Dose response of the intravascular contrast agent gadofosveset trisodium in MR perfusion imaging of the myocardium using semiquantitative evaluation. Issue 1 (2nd October 2013) - Niedermayer, Sebastian; Prompona, Maria; Cyran, Clemens C.; Reiser, Maximilian; Huber, Armin
<x xml:space="preserve">Abstract</x> Purpose To evaluate appropriate injection protocols for gadofosveset at 1.5 and 3 T magnetic resonance imaging (MRI) for semiquantitative myocardial perfusion analysis. Materials and Methods Eighteen young healthy volunteers were subjected to first‐pass perfusion cardiac scans at 1.5 and 3 T MRI using three different injection protocols for gadofosveset (0.00375, 0.0075, and 0.0150 mmol/kg bodyweight) and two perfusions. At both field strengths a T1‐weighted saturation recovery turboFLASH sequence with parallel imaging was employed. Peak signal‐to‐noise ratio (SNR), maximum contrast enhancement ratio (CER), peak‐baseline difference, and upslope values were assessed. Moreover, sectors with dark banding artifacts were evaluated. Results Significant differences of the upslope values for first compared to second perfusion could be observed for the medium‐ and high‐dose groups at 1.5 T (P < 0.01), but not at 3 T. Sectors with dark banding artifacts during first perfusion occurred significantly more often at the highest dose of gadofosveset compared to the lowest dose at 1.5 T (P = 0.04) and 3 T (P < 0.01). Conclusion The best injection protocol for semiquantitative perfusion analysis at 1.5 T is 0.00375 mmol/kg, as higher doses lead to lower upslope values during the second perfusion. At 3 T 0.0075 mmol/kg should be used to avoid dark banding artifacts. J. Magn. Reson. Imaging 2014;39:203–210. © 2013 Wiley Periodicals, Inc.